Studies of the glaciers located on the Verkhneangarsky mountain range - M. D. Ananicheva; G. Yu. Pakin; A. L. Entin (Лëд и снег, 2019)
Glaciers of the Verkhneangarsky mountain range are discovered in 2017-2018 and require detailed investigation and cataloging. This group of glaciers includes glaciers of the corrie and morphological types, and, according to the sizes, they should be qualified as small forms of glaciation. Four glacial formations were found during field studies of 2017-2018 together with several snow patches and stone glaciers; these four glaciers were measured and described. The temperature of ice in the glaciers of this region was measured during the investigations. Data on the ice temperature close to the temperature of the surface permafrost layer explain one of the conditions for existence of glaciers in the temperate zone at altitudes of 1800-2000 m. The dynamics of some glacial formations is analyzed in comparison with their present-day sizes, obtained as a result of interpretation of images from Bing maps and Sentinel-2 services, as well as with images of the CORONA mission (1967). The relative stability of the local glacial formations under climate change is related to the underlying permafrost as well as to the forms of occurrence in the relief, and a degree of closure by the stone cover.